2008
DOI: 10.1523/jneurosci.1056-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for Frizzled5 in Neuronal Survival in the Parafascicular Nucleus of the Thalamus

Abstract: Frizzled5 (Fz5), a putative Wnt receptor, is expressed in the retina, hypothalamus, and the parafascicular nucleus (PFN) of the thalamus. By constructing Fz5 alleles in which ␤-galactosidase replaces Fz5 or in which Cre-mediated recombination replaces Fz5 with alkaline phosphatase, we observe that Fz5 is required continuously and in a cell autonomous manner for the survival of adult PFN neurons, but is not required for proliferation, migration, or axonal growth and targeting of developing PFN neurons. A motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 78 publications
(87 reference statements)
4
27
0
Order By: Relevance
“…Thus, increases of -catenin function in ventral mesencephalic precursors result in increased dopamine neuron differentiation [61]. These results fit perfectly with recent data demonstrating that downregulation of -catenin levels could be part of the mechanisms involved in the neuronal loss characteristic of neurodegenerative diseases such as Parkinson´s disease [62].…”
Section: A) Beta-catenin Is a Downstream Target Of The Ptn/rptp / Sigsupporting
confidence: 89%
“…Thus, increases of -catenin function in ventral mesencephalic precursors result in increased dopamine neuron differentiation [61]. These results fit perfectly with recent data demonstrating that downregulation of -catenin levels could be part of the mechanisms involved in the neuronal loss characteristic of neurodegenerative diseases such as Parkinson´s disease [62].…”
Section: A) Beta-catenin Is a Downstream Target Of The Ptn/rptp / Sigsupporting
confidence: 89%
“…Recent studies have found that PF neurons, in addition to using glutamate as a transmitter, express certain other proteins, including cerebellin1 (Cbln1; Kusnoor et al, 2010), the leucine-rich repeat-containing G protein coupled receptor 8 (LGR8; Sedaghat et al, 2008), and frizzled5 (Fz5), a wnt receptor (Liu et al, 2008). Interestingly, conditional knockouts of Fz5 lead to loss of PF neurons (Liu et al, 2008), suggesting at least one mechanism independent of dopamine signaling that may contribute to degeneration of PF neurons in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, conditional knockouts of Fz5 lead to loss of PF neurons (Liu et al, 2008), suggesting at least one mechanism independent of dopamine signaling that may contribute to degeneration of PF neurons in PD.…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, Fz5 is expressed selectively in neurons in the parafascicular nucleus (PFN) of the thalamus, and Fz5 CKO/CKO ;Sox2-Cre mice show a progressive loss of PFN neurons over the first several months of postnatal life (Liu, Wang, Smallwood, & Nathans, 2008). Genetic mosaic experiments in which Fz5 −/− cells are marked by expression of a reporter show that this loss is cell autonomous.…”
Section: Frizzled5 and Frizzled8mentioning
confidence: 99%
“…Numerous changes in gene expression in PFN neurons precede neuronal loss, including downregulation of the genes coding for beta-catenin, Wnt4, and Wnt9b, suggesting that a Fz5-dependent positive feedback loop maintains canonical Wnt signaling in the PFN. The physiological role of the PFN is not well understood, but the work of Liu et al (2008) implicates the PFN in sensorimotor function because loss of PFN neurons in Fz5 CKO/CKO ;Sox2-Cre mice is accompanied by impaired motor coordination.…”
Section: Frizzled5 and Frizzled8mentioning
confidence: 99%